A Molecular‐Switch‐Embedded Organic Photodiode for Capturing Images against Strong Backlight. Issue 17 (18th March 2022) - Kang, Mingyun; Hassan, Syed Zahid; Ko, Seong‐Min; Choi, Changwon; Kim, Juhee; Parumala, Santosh K. R.; Kim, Yun‐Hi; Jang, Yun Hee; Yoon, Jinhwan; Jee, Dong‐Woo; Chung, Dae Sung
Abstract: When the intensity of the incident light increases, the photocurrents of organic photodiodes (OPDs) exhibit relatively early saturation, due to which OPDs cannot easily detect objects against strong backlights, such as sunlight. In this study, this problem is addressed by introducing a light‐intensity‐dependent transition of the operation mode, such that the operation mode of the OPD autonomously changes to overcome early photocurrent saturation as the incident light intensity passes the threshold intensity. The photoactive layer is doped with a strategically designed and synthesized molecular switch, 1, 2‐bis‐(2‐methyl‐5‐(4‐cyanobiphenyl)‐3‐thienyl)tetrafluorobenzene (DAB). The proposed OPD exhibits a typical OPD performance with an external quantum efficiency (EQE) of <100% and a photomultiplication behavior with an EQE of >100% under low‐intensity and high‐intensity light illuminations, respectively, thereby resulting in an extension of the photoresponse linearity to a light intensity of 434 mW cm −2 . This unique and reversible transition of the operation mode can be explained by the unbalanced quantum yield of photocyclization/photocycloreversion of the molecular switch. The details of the operation mechanism are discussed in conjunction with various photophysical analyses. Furthermore, they establish a prototype image sensor with an array of molecular‐switch‐embedded OPD pixels to demonstrate their extremely high sensitivity against strong light illumination. Abstract : A molecular‐switch‐embedded organic photodiode exhibits an autonomous transition of the operation mode between photovoltaic‐ and photomultiplication‐type photodiodes, resulting in the extension of the photoresponse linearity to 434 W cm −2 . This mechanism is enabled by the light‐intensity‐adjusted cyclization–cycloreversion equilibrium of diarylethene‐based molecular switches. Consequently, prototype image sensors with reliable sensitivity against strong backlight are demonstrated.